The long fall [compact disc, unabridged] - Mosley, Walter (Mosley, Walter. Leonid McGill mysteries., 2009)
Ex-boxer, hard drinker, in a business that trades mostly in cash and favors, Leonid McGill is an old-school P.I. working a city that's gotten fancy all around him. And like New York City itself, McGill is turning over a new leaf, "decided to go from crooked to slightly bent." But when he calls in old markers and greases a few NYPD palms to unearth some seemingly harmless information for a high-paying client, he learns that even in this cleaned-up city, his commitment to the straight and narrow is going to be constantly tested.